ArcView GIS : the geographic information system for everyone (ESRI, 1996)
Desktop geographic information system for storing, modifying, querying, analyzing, and displaying data. Links with any SQL DBMS, ASCII, dBASE or INFO files. Features Avenue object-oriented programming language. Includes views, editable map legend, feature-based text labels, database queries, synchronous selection environment, multiple map displays, address matching and geocoding, intelligent map redraw, and set of sample data.